5-Methoxy-2- (2-morpholinoethyl)iminiomethyl phenolate - Lair, N.M.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
Each of the two independent molecules of the title comound, C(14)H(20)N(2)O(3), exists in the zwitterionic form as the imino N atoms are protonated. The = N-H unit forms an intramolecular hydrogen bond to the negatively charged O atom, and also a weaker intermolecular N-H center dot center dot center dot O bond, the latter resulting in inversion dimers.